2018
DOI: 10.3892/or.2018.6558
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of IQGAP1 promotes the angiogenesis of esophageal squamous cell carcinoma through the AKT and ERK‑mediated VEGF‑VEGFR2 signaling pathway

Abstract: Angiogenesis is crucial for the progression of esophageal squamous cell carcinoma (ESCC). Anti‑angiogenesis by targeting important molecules has been considered as one of the most promising and efficient strategy for cancer therapy. Recent studies have demonstrated that the IQ‑domain GTPase activating protein 1 (IQGAP1) plays critical roles in tumorigenesis and cancer progression. We previously reported that IQGAP1 is overexpressed in ESCC, and IQGAP1 knockdown can decrease cell proliferation and metastasis ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…MMP-2 and MMP-9 remodel extracellular matrix and contribute to cell invasion, and VEGF-A promotes angiogenesis in various malignancies [ 6 ]. In ESCC, MMP-2 and MMP-9 contribute to tumor invasion and metastasis [ 58 , 59 ], and VEGFs including VEGF-A contribute to angiogenesis and are associated with high microvascular density and poor patient prognosis [ 60 62 ]. MMP-2 is involved in CCL3-dependent cell invasion in oral squamous cell carcinoma [ 27 ] and chondrosarcoma [ 21 ], whereas MMP-9 is involved in CCL3-dependent cell invasion in hepatocellular carcinoma [ 17 ] and oral squamous cell carcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-2 and MMP-9 remodel extracellular matrix and contribute to cell invasion, and VEGF-A promotes angiogenesis in various malignancies [ 6 ]. In ESCC, MMP-2 and MMP-9 contribute to tumor invasion and metastasis [ 58 , 59 ], and VEGFs including VEGF-A contribute to angiogenesis and are associated with high microvascular density and poor patient prognosis [ 60 62 ]. MMP-2 is involved in CCL3-dependent cell invasion in oral squamous cell carcinoma [ 27 ] and chondrosarcoma [ 21 ], whereas MMP-9 is involved in CCL3-dependent cell invasion in hepatocellular carcinoma [ 17 ] and oral squamous cell carcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A is involved in CCL3-dependent angiogenesis in osteosarcoma [ 23 ] and is also upregulated downstream of the CCL3–CCR5 axis in oral squamous cell carcinoma [ 27 ]. Activating the PI3K/Akt and MEK/ERK pathways induces the expressions of MMP-2, MMP-9, and VEGF-A in various malignancies including ESCC [ 62 65 ]. Our present results demonstrated that treatment with rhCCL3 upregulated the MMP2 mRNA expression in three ESCC cell lines universally, and the VEGFA mRNA expression in two ESCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP1 is reported to be upregulated in many human cancers and associated with enhanced malignant behaviours. [42][43][44] In contrast, the characteristics of IQGAP3 are less studied, though it may have a role similar that of to IQGAP1 in tumorigenesis. In our study, we compared IQGAP3 expression in 40 paired CRC tissues, which provided important evidence showing IQGAP3 to be upregulated in CRC tissue.…”
Section: Discussionmentioning
confidence: 99%
“…6 The growth and progression of solid tumors, including esophageal cancer, depend on tumor angiogenesis. 7 Anti-angiogenesis therapy has also been proven to be an effective strategy for the treatment of solid tumors. VEGF is the main angiogenesis promoting factor; therefore, anti-VEGF treatment is an effective anti-angiogenesis treatment strategy of tumors.…”
Section: Introductionmentioning
confidence: 99%